On the implementation of the Special Justice for Peace in Colombia: a reflection on the opposition forces and their interest in slowing the transition - Flórez Vargas, Carlos Albeiro (DIXI, 2019)
Objective: this article is an invitation to reflect on the stratagems that seek to limit or annul the actions of the Special Justice for Peace (jep). Also, about the harmful consequences of these practices not only for society, but even for those who promote them.Methodology: in order to reflect on these positions, it is important to consider the different models of transitional justice.Results: in an internal conflict like the Colombian one, which flooded a whole country with violence for more than 50 years, many actors intervene. Among these, some have been fully recognized, while others remain anonymous. On the one hand, within the first group, there are many ex-militants (both from the State Military Forces as well as from the insurgency and from paramilitary groups) interested in resolving their legal situation through the Special Justice Tribunal for Peace (JEP). On the other hand, those who have not been prosecuted, condemned or even publicly exposed as responsible for acts of violence in the context of the conflict, deploy a whole series of strategies in order to prevent the transition process from being effective.Conclusions: political blindness, in a perverse conspiracy with ignorance about the explanatory principles and models that guide transitional justice, clouds any rationality that allows the effective transition from a society with an internal conflict to one with a stable and lasting peace.
Keywords: conflict actors; bureaucracy; transitional justice; reparation and non-repetition; civilian third parties; victim and victimizers